Challenges in Diagnosing Myelodysplastic Syndromes in the Era of Genetic Testing: Proceedings of the 13th Workshop of the European Bone Marrow Working Group - Hebeda, Konnie M; Tzankov, Alexandar; Boudova, Ludmila; Saft, Leonie; Hasserjian, Rob P; de Boer, Mirthe; Fend, Falko; Orazi, Attilio; Leguit, Roos (Pathobiology, 2019)
The 13th workshop of the European Bone Marrow Working Group in Utrecht, The Netherlands, was devoted to studying myelodysplastic syndromes (MDS) and their boundaries. The panel received 44 cases submitted to the 3 invited categories, which included: reactive cytopenias with dysplasia, idiopathic cytopenia of undetermined significance, clonal haematopoiesis of indeterminate potential, idiopathic dysplasia of uncertain significance and overt MDS. For this summary, we have selected 17 cases that highlight difficulties in separating true MDS from other causes of cytopenia and the intricate relationship between clonal haematopoiesis and true MDS. In addition, cases of overt MDS with challenging features were also selected. All cases were stained for p53 expression. Using instructive submitted cases we discuss the following: (1) cytopenia with clonal haematopoiesis not fulfilling MDS criteria, (2) cytopenia and/or dysplasia with germline mutations and/or familial history suggesting an underlying gene defect, (3) MDS based on a recurrent chromosomal abnormality and (4) overt MDS with diagnostic difficulties due to concurrent treatment or disease. The lively discussion in the open forum of the workshop illustrated the need for better integrative understanding of the evolution of acquired genetic abnormalities in haematopoiesis, and the challenge of diagnosing true MDS in cytopenic patients with genetic abnormalities, either germline or acquired.
Keywords: Genetic Testing; Workshop; Male; výchova a vzdělávání; genetické testování; High-Throughput Nucleotide Sequencing; Adolescent; Myelodysplastic Syndromes; Sequence Analysis, DNA; chromozomální aberace; sekvenční analýza DNA; Adult; Aged; dospělí; Classification; mužské pohlaví; senioři; Myelodysplastic syndrome; mladiství; Cytopenia; myelodysplastické syndromy; Chromosome Aberrations; senioři nad 80 let; lidé; ženské pohlaví; Humans; Bone marrow; vysoce účinné nukleotidové sekvenování; Bone Marrow; Next-generation sequencing; kostní dřeň; Aged, 80 and over; Education; Female; lidé středního věku; Middle Aged